Online teaching portfolio as a catalyst for professional development - Bokiev, Umed; Bokiev, Daler; Othman, Moomala; Ismail, Lilliati; Aralas, Dalia (Human Resource Management Academic Research Society, 2017)
In today’s world that is constantly changing with new technologies, teachers are faced with significant challenges which they can meet by engaging in optimal professional development. As an effective tool to deepen teachers’ understanding of their role and prospects, teaching portfolios have been traditionally used in teacher education and development. Made possible by recent technological innovations, online teaching portfolios have naturally emerged as a value-added form of professional development to be employed by teachers who are willing to respond to the constant changes in our digital age. The present paper aims to analyse the role, potential and advantages of online teaching portfolios within the context of teacher professional development in view of current research and literature, as compared to traditional paper-based teaching portfolios. Research findings suggest that the advantages and positive effects of utilizing online teaching portfolios on professional development outweigh the drawbacks and difficulties encountered by teachers. Online teaching portfolios not only spur reflection, creativity and collaboration among teachers, but also yield such complementary benefits as the enhancement of their social and linguistic competences as well as ICT skills. The employment of online teaching portfolios perfectly captures the very nature of self-directed professional learning and provides a rationale for undertaking other forms of professional development. It is anticipated that the online teaching portfolio, if implemented within the Malaysian educational context, will catalyse the personal and professional growth of both in- service and pre-service teachers through its capacity to foster and maintain continuous development and reflection on competences and accomplishments.